EFEK PERAWATAN LUKA TERKONTAMINASI DENGAN EKSTRAK BAWANG PUTIH LANANG DALAM MEMPERCEPAT PENURUNAN ERITEMA - Wiji Utami, Yulian; Murniati, Anis; Sumarno, Sumarno (Jurnal Kedokteran YARSI, 2009)
This study was aimed to examine the effect of ?lanang? onion extract to accelerate the reduction of erythema inflammation sign in contaminated wound. A true experimental with posttest only control group design was used. The variable observed was a photograph of wound taken throughout the experiment which was then processed by program corel photopoint suite graphic 12, so it could provide average value of the decrease of erythema inflammation sign. Samples consisted of 4 groups, each group was composed of five rats. A series of extract concentration were applied, e.g. 128 mg/ml,256 mg/ml, and 512 mg/ml for the first, second and third group respectively. In addition, 10% povidone iodine was used for the forth group. The result showed that by the eighth day, the average decrease of mean red color intensity or the erythema values were 49.26, 45.44, 45.32 and 62. 96 in the first, second, third and forth group respectively. Statistical analysis employing one way ANOVA showed significant difference for all groups [o.ooo (0.05)]. No different was observed on Post hoc result test in group 1 and 2 [0.352 (0.05)], however, significant difference [0,0000 (0,05)] was found between group 1 and 3, group 1 and 4, group 2 and 3, group 2 and 4, group 3 and 4. Employing simple regression correlation, significance correlation of less than 0.05 and R 0.705 was found for the extract in reducing the erythema. It was concluded that ?Lanang? onion extract was better in accelerating the reduction of erythema inflamation sign than that with povidone iodine. It was suggested that further studies particularly using microbiology method were still required to prove this finding.